Modeling the integration of ethics, social responsibility, and sustainability in university contexts - John William Atehortúa-Mosquera; Iliana Ramírez-Velásquez (PLoS ONE, 2025)
The integration of ethics, social responsibility, and sustainability (ERS) into higher education curricula is essential for fostering competencies aligned with the Sustainable Development Goals. This study aimed to develop and validate a structural model to evaluate ERS competencies in higher education. Data were collected from a sample of 418 engineering students at a public university in Colombia, using a Likert-type instrument comprising items distributed across three dimensions. Exploratory factor analysis identified a well-defined three-factor structure, while confirmatory factor analysis confirmed the model’s validity. The structural equation model demonstrated a good fit (CFI = 0.946, TLI = 0.940, RMSEA = 0.047, SRMR = 0.042), and reliability analysis indicated excellent internal consistency (α = 0.914; ω = 0.920 for the higher-order ERS construct). Results showed that ERS significantly explained the first-order dimensions of Ethics (0.620), Sustainability (0.884), and Social Responsibility (0.847). Moreover, ERS predicted academic performance in transversal courses, with standardized coefficients of 0.698 in Science, Technology, and Society (STS) and 0.574 in Environmental Management (p < .001). These findings provide strong empirical support for the hierarchical structure of ERS competencies, confirm their positive association with academic achievement, and highlight the model’s value as a tool to guide curriculum development and policy in higher education.